Adoption of a child - an act of noble character - Anastasov, Blagojche; Kochoska, Jasminka (Technium Social Sciences Journal, 2020)
Adopting a child is a truly emotionally difficult decision for any human being. To be a true parent, it is not necessary to be a biological parent. True parents are not those who give birth, but those who devote the best years of their lives to raising a wonderful child. Adoption is a noble act for adopted children, adoptive parents, his extended family and community. Its impact is generational, with a long-term benefit, as it will affect future generations of the family. For a number of children, adoption is the only way to have a family, and for a number of people the only opportunity to be realized as parents. There are a number of advantages to adopting a child, but in our society, it is still a concept that is misunderstood. Even today, this topic is not often discussed; it is avoided and almost never mentioned in education. Therefore, we must take the initiative and continue to learn how adoption is valuable and important to everyone.